Migration and the Historical Development of Islam in Taiwan from the 17th to the Early 21st Century - Rahmawati, Fitri; Azizah, Faras Puji; Nelmawarni, Nelmawarni; Erman, Erman (Regalia Institute, 2023)
The spread of Islam in Taiwan is inseparable from the history of Islam's entry into Tiongkok, which began with the migration of Chinese Muslims to Taiwan in the 17th century and was followed by subsequent migrations. This research analyses the phases and influences brought by Muslim migrants to Taiwan. The method used in this research is the historical research method, including heuristics, source criticism, interpretation and historiography. The results of this study show that there are four phases of Muslim migration to Taiwan: the first phase occurred in the 17th century, the second phase 1952-1961 which occurred in two waves, the first wave 1952-1954, the third phase occurred in 1961, this phase is also known as the evacuation phase of KMT Veterans from Burma and Thailand. The fourth phase occurred in 1989, with the influx of migrant workers from Tiongkok, Burma, Thailand, Indonesia and Malaysia; these immigrants positively impacted the development of Islam in Taiwan. Evidence of the development of Islam in this fourth phase is the existence of halal certification, halal restaurants and hotels, Muslim-friendly neighborhoods, the establishment of the Indonesian Mosque (Masjid At-Taqwa), the emergence of Muslim communities (FORMMIT, Chinese Muslim Association, Indonesian Student Association) and the presence of Indonesian Muslim organizations (Nahdlatul Ulama and Muhammadiyah).